AgNPs treatment reduces time recovery and increases bacterial sensitivity to antibiotics in cow´s purulent catarrhal endometritis. A translational study; PLoS One; Vol. 20, iss. 10 - Huerta-Saquero A. Alejandro; Nefedova E. Ekaterina; Shkil N. Nikolay; Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N. Nina (2025, 2025)
Title screen